Nutrient roadmap (Water Environment Federation, 2015)
The Nutrient Roadmap provides a path forward for the wastewater sector on nutrient removal and recovery and challenges water resource recovery facilities to have a zero net impact with regard to nutrient discharges by 2040. This high-level overview provides guidance for utilities of all sizes to best manage nutrients in the context of their individual regulatory climates. The Nutrient Roadmap informs future research, training, and advocacy programs to support the movement towards smarter nutrient management in water resource recovery facilities. 184 pages. Table of Contents Executive Summary Chapter 1: Introduction Chapter 2: Setting the Stage for Nutrient Management Chapter 3: Understanding the Environment Chapter 4: Resource Recovery Chapter 5: Alternatives Evaluation Chapter 6: Identifying and Managing Risks Chapter 7: Case Studies Chapter 8: Conclusions.
"P150002"--Back cover
Keywords: Sewage -- Purification -- Nutrient removal.; Sewage -- Purification -- Nitrogen removal.; Sewage -- Purification -- Phosphate removal.; elektronické knihy; electronic books